Successful management of dystocia in Holstein Friesian cow due to hydrocephalic fetus – a case report - Arunpandian, J; Srivastava, Neeraj; Neethu, B; Kujur, Anju (Animal Reproduction Update, 2022)
Hydrocephalus is a congenital condition caused by excessive accumulation of cerebrospinal fluid in the cranial cavity and this condition is reported less frequently in mammals. A 6 year-old Holstein Friesian cow was presented with the history of straining for 15 hours with rupture of water bag, but failure in expulsion of foetus. Per vaginal examination revealed hydrocephalic foetus without corneal and pedal reflex. This case was diagnosed as dystocia due to hydrocephalus condition in the foetus. The dystocia was relieved manuallyby evacuating the fluid by incising around the head region followed by application of traction force. Thereafter the animal was treated for three days with fluid therapy, broad spectrum antibiotic and anti-inflammatory drugs.